Motor coordination: influence of age, sex, socio-economic status and levels of adiposity, in peruvian children - Alcibiades Bustamante Valdivia; Liz Caballero Cartagena; Natalia Enciso Sarria; Ingrid Salazar Távara; André F. Teixeira e Seabra; Rui Manuel Garganta da Silva; José António Ribeiro Maia (Universidade Federal de Santa Catarina, 2008)
The objective of this study was to describe motor coordination (CoM) levels, in addition to the infl uence of age, socioeconomic status (SES), sex and subcutaneous adiposity on the CoM of Peruvian children aged six to eleven years. The sample size was 4007 children (n=1889 females; n=2118 males) from several schools in the metropolitan area of Lima, Peru. CoM was assessed with the KTK (Kiphard and Schilling, 1974) test battery that includes 4 tests: balancing backward (BB), hopping on one leg (HO), jumping sideways (JS) and shifting platforms (SP). Subcutaneous adiposity included the sum of several skinfolds: triceps, subscapular and calf. Socioeconomic status (SES) was evaluated according to the physical location of each school (type of neighborhood). Exploratory, descriptive and inferential statistical analyses (ANOVA II as well as regression linear models) were performed using SPSS 15. Signifi cant increases in mean values of CoM were observed in both sexes and across age. Children with high adiposity exhibited lower performance in all tests. Boys outperformed girls. High SES has a greater infl uence only on HO, and a low SES proved relevant to BB performance. It can be concluded that CoM is highly specifi c to each gender. Body fat levels have a negative infl uence on each coordination test, as well as on overall coordination. SES does not seem to be a conclusive predictor of motor coordination in children.